RETRACTED: Immobilization of metribuzin-degrading bacteria on biochar: Enhanced soil remediation and bacterial community restoration - Wahla, Abdul Qadeer; Anwar, Samina; Fareed, Muhammad Irfan; Ikram, Wasiq; Ali, Liaqat; Alharby, Hesham F.; Bamagoos, Atif A.; Almaghamsi, Afaf A.; Iqbal, Samina; Ali, Shafaqat (Frontiers in Microbiology, 2023)
Metribuzin (MB), a triazinone herbicide is extensively sprayed for weed control in agriculture, has been reported to contaminate soil, groundwater, and surface waters. In soil, MB residues can negatively affect not only the germination of subsequent crops but also disturb soil bacterial community. The present study describes the use of biochar as a carrier material to immobilize MB degrading bacterial consortium, for remediation of MB contaminated soil and restoration of soil bacterial community in soil microcosms. The bacterial consortium (MB3R) comprised of four bacterial strains i.e., Rhodococcus rhodochrous AQ1, Bacillus tequilensis AQ2, Bacillus aryabhattai AQ3 and Bacillus safensis AQ4. Significantly higher MB remediation was observed in soil augmented with bacterial consortium immobilized on biochar compared to the soil augmented with un-immobilized bacterial consortium. Immobilization of MB3R on biochar resulted in higher MB degradation rate (0.017 Kd-1) and reduced half-life (40 days) compared to 0.010 Kd-1 degradation rate and 68 day half-life in treatments where un-immobilized bacterial consortium was employed. It is worth mentioning that the MB degradation products metribuzin-desamino (DA), metribuzin-diketo (DK) and metribuzin desamino-diketo (DADK) were detected in the treatments where MB3R was inoculated either alone or in combination with biochar. MB contamination significantly altered the composition of soil bacteria. However, soil bacterial community was conserved in response to augmentation with MB3R immobilized on biochar. Immobilization of the bacterial consortium MB3R on biochar can potentially be exploited for remediation of MB contaminated soil and protecting its microbiota.